2013
DOI: 10.1111/sjop.12032
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive control deficits in adolescents born with very low birth weight (≤ 1500 g): Evidence from dichotic listening

Abstract: The objective of the paper is to explore bottom-up auditory and top-down cognitive processing abilities as part of long-term outcome assessment of preterm birth. Fifty-five adolescents (age 13-15) born with very low birth weight (VLBW) were compared to 80 matched controls born to term, using three consonant-vowel dichotic listening (DL) instruction conditions (non-forced, forced-right and forced-left). DL scores were correlated with cortical gray matter thickness derived from T1-weighted structural MRI volumes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 58 publications
(72 reference statements)
1
5
0
Order By: Relevance
“…This provides novel insight to prior reports that VLBW individuals have excessive attention towards irrelevant stimuli/dis-tractors (Aasen et al, 2016; van de Weijer-Bergsma et al, 2008). Moreover, the fact that VLBW individuals displayed a predominantly hyper-reactive brain activation signature, is in line with prior studies reporting that they have problems with top-down modulation of cognitive control processes (Bless et al, 2013; Geldof et al, 2013; Pizzo et al, 2010), while bottom-up processes such as altering and the orienting response often remain intact (Geldof et al, 2013; Pizzo et al, 2010). Facilitation of performance through top-down processes is believed to be associated with successful implementation of perceptual, motor- and attentional task-sets, and is linked to neural activation within a fronto-parietal system (Corbetta and Shulman, 2002).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This provides novel insight to prior reports that VLBW individuals have excessive attention towards irrelevant stimuli/dis-tractors (Aasen et al, 2016; van de Weijer-Bergsma et al, 2008). Moreover, the fact that VLBW individuals displayed a predominantly hyper-reactive brain activation signature, is in line with prior studies reporting that they have problems with top-down modulation of cognitive control processes (Bless et al, 2013; Geldof et al, 2013; Pizzo et al, 2010), while bottom-up processes such as altering and the orienting response often remain intact (Geldof et al, 2013; Pizzo et al, 2010). Facilitation of performance through top-down processes is believed to be associated with successful implementation of perceptual, motor- and attentional task-sets, and is linked to neural activation within a fronto-parietal system (Corbetta and Shulman, 2002).…”
Section: Discussionsupporting
confidence: 87%
“…In the VLBW population, deficits in a broad range of cognitive domains are reported, and cognitive control dysfunction is prevalent (Bless et al, 2013; Lohaugen et al, 2010; Ostgard et al, 2016). Cognitive control processes in the brain operate on (at least) two different temporal scales (Braver, 2012; Dosenbach et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, our results are consistent with findings from chicks and rodents, showing that premature light exposure leads to altered auditory processing 5 6 61 62 . Similarly, despite normal audiometric thresholds, preterm infancy is correlated with a large range of auditory-based disorders including delayed language acquisition 63 64 65 66 67 68 . Therefore, we suggest that early exposure to light in preterm infants could lead to the premature closure of the auditory CP during an epoch of brain maturation vital to the development of normal auditory processing.…”
Section: Discussionmentioning
confidence: 99%
“…A study in very low birth weight adolescents showed weaker performance of the right ear in both a free recall condition and a condition in which children were asked to focus on the right ear, but these differences were not significant. 24 However, to the knowledge of the authors, dichotic listening has never been studied in VPT school-aged children, and therefore, it is still unknown whether dichotic listening performance is associated with language performance in VPT children. Furthermore, as dichotic listening requires interhemispheric exchange during this task, 20 it might be associated with microstructural CC characteristics.…”
Section: Introductionmentioning
confidence: 99%